Women in Charge: Evidence from Hospitals - LEWELLEN, KATHARINA (Journal of Finance, 2025)
ABSTRACT The paper examines the decision‐making, compensation, and turnover of female CEOs in U.S. hospitals. Contrary to the literature on lower‐ranked executives and directors in public firms, there is no evidence that gender differences in preferences for risk or altruism affect decision‐making of hospital CEOs: corporate policies do not shift when women take (or leave) office, and male and female CEOs respond similarly to a major financial shock. However, female CEOs earn lower salaries, face flatter pay‐for‐performance incentives, and exhibit greater turnover after poor performance. Hospital boards behave as though they perceive female CEOs as less productive.